Functional gastrointestinal disorders negatively affect health-related quality of life in MS. Issue 5 (October 2019) - Marrie, Ruth Ann; Leung, Stella; Tyry, Tuula; Cutter, Gary R.; Fox, Robert; Salter, Amber
Abstract : Objective: To determine the prevalence of functional gastrointestinal disorders, the demographic and clinical characteristics associated with the presence of functional gastrointestinal disorders, and the effects of these disorders with health-related quality of life (HRQOL) in a large, diverse population of persons with MS. Methods: In 2014, we surveyed participants in the North American Research Committee on Multiple Sclerosis registry regarding functional gastrointestinal disorders using the Rome III questionnaire. Participants also reported their sociodemographic characteristics, disability status using Patient Determined Disease Steps, the presence of comorbid depression and anxiety, health behaviors, and HRQOL using the RAND-12. We determined the prevalence of each gastrointestinal disorder using the Rome III criteria. Using multivariable logistic regression models, we assessed the factors associated with the presence of each bowel disorder. Using linear regression, we evaluated the association between functional gastrointestinal disorders and HRQOL. Results: Of 6, 312 eligible respondents, 76.5% were female, with a mean (SD) age of 58.3 (10.2) years. Forty-two percent of respondents (n = 2, 647) had a functional gastrointestinal disorder, most often irritable bowel syndrome (IBS), which affected 28.2% of participants. The prevalence of all functional gastrointestinal disorders increased with greater disability, and the prevalence of IBS increased with longer disease duration. After adjusting for sociodemographic and clinical characteristics, functional gastrointestinal disorders were associated with lower physical and mental HRQOL (both p < 0.0001). Conclusions: Functional gastrointestinal disorders are common in MS and are associated with reduced HRQOL.